Narasi Cerita Rakyat Riau “Asal Mula Penamaan Pulau Matang dan Pulau Keras” - Laras Anindya; Ahmad Jum’a Khatib Nur Ali (Pusat Studi Bahasa dan Publikasi Ilmiah, 2019)
Folktales are stories that have been told generation to generation within the society. It commonly consisting of moral and life values. To understand such values this research focused on finding the narrative function and structure. The research use Asal Mula Penamaan Pulau Matang dan Pulau Keras a Riau Province folktale as research object. The research employs qualitative method and theories of narrative structure by Tzetvan Todorov and narrative function by Vladimir Prop as tools of analysis. The results are Asal Mula Penamaan Pulau Matang dan Pulau Keras employs Equilibrium, Disruption, Recognition, Repair the Damage, and New Equilibrium as narrative structure. It also employs six (6) of Propp narrative function concept they are; Mediation, The Hero’s Reaction, Struggle, Victory, and Wedding